Expérience et empathie chez Bernard de Clairvaux - Falque, Emmanuel (Revue des sciences philosophiques et théologiques, 2005)
Experience and empathy define two great quests of contemporary phenomenology, one in the thought of Edmond Husserl, the other in the thought of Max Scheler. In an altogether different order and according to an altogether different perspective, Bernard of Clairvaux appears here as the pioneer: in his conceptualization of experientia on the one hand and his reflection upon compassio on the other. Far from pursuing a negative denunciation of metaphysics, we will attempt to show here how, positively in this instance, metaphysics opens upon another « type of discourse » and displays the « possibles » to be reexamined today. Supported by a rereading of the Sermons on the Canticle and the Treatise on the Love of God, the application of the « field of experience », the novelty of « language of affect », and man’s amorous empathy » with God, thus constitute the different moments of a possible philosophical rediscovery of Cistercian mysticism for our time.